Climate Change Education in the Context of Education for Sustainable Development: Rationale and Principles: - Mochizuki, Yoko; Bryan, Audrey (Journal of Education for Sustainable Development, 2015)
Although the role of education in addressing the challenges of climate change is increasingly recognized, the education sector remains underutilized as a strate...